Pengaruh Harga dan Kualitas Pelayanan pada Kepuasan Konsumen Alfamart dan Indomaret - Aisyah, Siti (Keizai, 2024)
Alfamart and Indomaret have a strong marketing strategy that extends to the standard of service. Numerous establishments of Alfamart and Indomaret have made them the preferred small-scale retailers with similar business models. Even if the pricing strategy differs, Alfamart and Indomaret offer better products. The purpose of this study is to determine how prices and product quality at Indomaret and Alfamart affect customers' satisfaction. Using a quantitative approach, the population of this study consists of people who shop at Indomaret and Alfamart in Jalan Tjilik Riwut Pal. 2,5, Kabupaten Katingan, Provinsi Kalimantan Tengah, at least twice a week. About 90 respondents were selected for this study using the convenience sampling technique. Data analysis techniques include paired sample t-tests and multiple regression analysis. The study's findings indicate that prices and quality of products have a positive and significant impact on customers' purchases at Indomaret and Alfamart, thus as prices and quality of products improve, more customers will be satisfied. In addition, there are differences between the customer satisfaction levels of Indomaret and Alfamart, with Alfamart's customer satisfaction being higher.